2013
DOI: 10.1021/jm401365h
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Tumor Retention of a Radiohalogen Label for Site-Specific Modification of Antibodies

Abstract: A known limitation of iodine radionuclides for labeling and biological tracking of receptor targeted proteins is the tendency of iodotyrosine to rapidly diffuse from cells following endocytosis and lysosomal degradation. In contrast, radiometal-chelate complexes such as indium-111-1,4,7,10-tetraazacyclododecane-1,4,7,10-tetraacetic acid (In-111-DOTA) accumulate within target cells due to the residualizing properties of the polar, charged metal-chelate-amino acid adduct. Iodine radionuclides boast a diversity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 34 publications
2
30
0
Order By: Relevance
“…5 A) at 48 h post administration revealed that FcRn binding impairment by point mutations yielded ~3-fold signal reduction in tumor and most tissues, largely mirroring exposure. Consistent with previous work, far less tumor uptake was observed with the non-residualizing 125 I label than with 111 In-DOTA (31). Distribution of 125 I-7C2-TCO 6 and 125 I-7C2-HAHQ-TCO 6 (hatched blue and black, respectively, Supplementary Fig.…”
Section: Pharmacokinetics and Biodistributionsupporting
confidence: 89%
“…5 A) at 48 h post administration revealed that FcRn binding impairment by point mutations yielded ~3-fold signal reduction in tumor and most tissues, largely mirroring exposure. Consistent with previous work, far less tumor uptake was observed with the non-residualizing 125 I label than with 111 In-DOTA (31). Distribution of 125 I-7C2-TCO 6 and 125 I-7C2-HAHQ-TCO 6 (hatched blue and black, respectively, Supplementary Fig.…”
Section: Pharmacokinetics and Biodistributionsupporting
confidence: 89%
“…[295][296][297][298] Most of the optical thiol-selective fluorescent probes often used as sensors for monitoring biological processes are represented by maleimide-containing reagents. [299][300][301] Another testament to maleimide utility is its use in glycosylation, 302 radiolabelling, 303,304 studying protein interactions, [305][306][307][308] and quantitation of cysteine residues. 309,310 Despite its successful application as a reagent for the chemical modification of proteins, the irreversibility of maleimide's addition makes it impossible to regenerate the unmodified protein by controlled disassembly of the conjugate.…”
Section: Fig 20mentioning
confidence: 99%
“…3C). These findings are in line with the residualizing nature of 89 Zr(IV), which stays trapped inside tumor cells after receptor-mediated endocytosis and lysosomal tracer degradation (21,22). Notably, however, the 2 protein tracers showed different levels of nonspecific accumulation, either in the thyroid ( 125 I) or in the kidney ( 89 Zr), leading to high organ-to-tumor ratios there.…”
Section: Biodistribution Studiessupporting
confidence: 57%